2014
DOI: 10.1051/0004-6361/201323024
|View full text |Cite
|
Sign up to set email alerts
|

First results from the CALYPSO IRAM-PdBI survey

Abstract: Context. The earliest evolutionary stages of low-mass protostars are characterised by hot and fast jets which remove angular momentum from the circumstellar disk, thus allowing mass accretion onto the central object. However, the launch mechanism is still being debated. Aims. We would like to exploit high-angular (∼0. 8) resolution and high-sensitivity images to investigate the origin of protostellar jets using typical molecular tracers of shocked regions, such as SiO and SO. Methods. We mapped the inner 22 of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 39 publications
6
87
2
Order By: Relevance
“…Compact continuum emission along protostellar jets has already been observed in other sources (e.g. Gueth et al 2003;Maury et al 2010;Codella et al 2014); envelope emission or shock-heated dust along the jet have been suggested as possible explanations for the origin of these features. However, a larger statistically suitable sample is crucial in order to assess this issue.…”
Section: Continuum Emission: Source Multiplicity and Propertiesmentioning
confidence: 68%
See 2 more Smart Citations
“…Compact continuum emission along protostellar jets has already been observed in other sources (e.g. Gueth et al 2003;Maury et al 2010;Codella et al 2014); envelope emission or shock-heated dust along the jet have been suggested as possible explanations for the origin of these features. However, a larger statistically suitable sample is crucial in order to assess this issue.…”
Section: Continuum Emission: Source Multiplicity and Propertiesmentioning
confidence: 68%
“…Finally, jet variability, in particular episodic ejection (see e.g. Codella et al 2014), may also play a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations of IRAS 4B are dynamic range limited, causing convolution artifacts to appear around the compact continuum peak; these artifacts are not real (see text). Toward IRAS 2A, Codella et al (2014) reported two secondary continuum sources that are 2 and 2.4 away, one along the blueshifted outflow and one southwest of the main component. Tobin et al (2015a) show that IRAS 2A is a binary on 0 .…”
Section: Sample and Observationsmentioning
confidence: 99%
“…Recent observations show that SO can be used to image high-velocity protostellar jets, similar to a standard tracer such as SiO (Lee et al 2010;Tafalla et al 2010;Codella et al 2014b). However, only two protostellar jets have so far been clearly mapped in SO lines: HH 211 and NGC 1333-IRAS 2A, and estimates of the SO abundance have only been derived for HH 211.…”
Section: Introductionmentioning
confidence: 99%